Analysis Of Digital Marketing, Free Shipping, And Consumer Reviews On Purchase Decisions On Shopee (Case Study On Students Of Dian Nusantara University, Jakarta) - Tarmizi, Achmad; Abdullah, Muhamad Al Faruq (Jurnal Multidisiplin Sahombu, 2025)
This research aims to determine the positive influence of Digital Marketing, Free Shipping, and Consumer Reviews on purchasing decisions at Shopee: Case Study of Dian Nusantara University Students, Jakarta. Data collection in this research was carried out using a survey method by distributing 100 questionnaires using the sampling technique used in this research using accidental sampling technique. The accidental sampling technique is the withdrawal of a sample size if the exact population size is not known. This research uses multiple regression analysis with the SPSS version 26 program as a tool for processing and analyzing research results. Hypothesis test results show that Digital Marketing Variables have a significant effect on Purchasing Decisions at Shopee. The Free Shipping variable has no significant effect on purchasing decisions at Shopee. The Consumer Review variable has a significant influence on purchasing decisions at Shopee. And the digital marketing variables, free shipping and consumer reviews together (simultaneously) have a significant effect on purchasing decisions on Shopee.